American women and World War II - Weatherford, Doris (Edison, NJ : Castle Books, 2008)
"Of all the nation's wars, perhaps none was more important for the evolution of women's roles in American society than World War II. At no other time in history had the United States been faced with such a clear choice in tis wartime strategy: either draw women closer to the mainstream of military and industrial life or lose the war for the sake of outmoded attitudes and beliefs. 'American Women and World War II' tells the story of the whole body of American Women who answered their country's call, both on the home front and on the front lines" -- inside cover.
pt. 1. Be a nurse and see the world. Military nurses in battle -- Calling all nightingales -- pt. 2. The military woman. Duty calls-women enter the military -- You're in the army now-life in the camps -- What GI Jane learned -- The problems she faced -- The skeptics convert -- pt. 3. The new industrial woman. Recruitment of a new labor force -- Rosie the riveter rallies to new jobs -- Women's problem are production's problems -- Balancing act: managing job and home -- From blue collar to pink: women and industry change each other -- pt. 4. The home front. The normal housewife in abnormal times -- Volunteers and more -- Wartime wedding -- The waiting wife -- "The war departments regrets ...." -- pt. 5. Afterward.
Includes bibliographical references (p. 322-325) and index.
Keywords: World War, 1939-1945 -- Women -- United States; Women -- United States -- History -- 20th century